A pilot randomized control study comparing sustained low efficiency daily dialysis (SLEDD) with sustained low efficiency daily diafiltration (SLEDD-F) in patients with acute kidney injury (AKI) in Hospital Universiti Sains Malaysia (HUSM) outcome : effect on renal outcome - Wan Ahmad Kamil, Wan Mohd Rasis (2015)
Introduction: Acute kidney injury in critically ill patients requiring dialysis remains to be a burden to the population in terms of mortality and renal recovery. Renal recovery is important as dialysis dependant patient leads to chronic hemodialysis which is a major burden for patients, their families, and healthcare systems, and is associated with higher long-term mortality. The standard renal replacement therapy used worldwide is continuous renal replacement therapy i.e. continuous veno-venous hemofiltration or intermittent hemodialysis. Emerging modalities as an alternative such as sustained low efficiency daily dialysis (SLEDD) and sustained low efficiency daily diafiltration (SLEDD-f) have shown similar outcome in terms of renal recovery and mortality with shorter duration of dialysis. These two therapies have not been directly compared. Methodology: This is a pilot randomized control study comparing two dialysis modalities (SLEDD vs SLEDD-f) for the treatment of AKI in the critical patients at HUSM. Duration of study is from 1st May 2014 till 1st November 2014 and a total of 12 patients were selected. Primary outcome measures were renal recovery at 42 days either complete, partial or no recovery. Secondary outcome measures all-cause mortality rate after 60 days of randomization. Results: Baseline characteristics of 12 patients randomized into two groups of 6 patients each were similar. Sepsis represented the major cause of acute kidney injury, 83.33% causes. The overall renal recovery for either SLEDD or SLEDD-f was 33.33%. In the SLEDD group, 20.0% of study subjects had complete renal recovery, while 80% were dialysis dependant. In the SLEDD-f group 50% of patients had complete renal recovery while the rest were dialysis dependant. There were no significant differences in the renal recovery outcome for both modalities (odds ratio, 4.00; 95% CI 0.27 to 6.33; p=0.317). Mortality within 60 days were observed in two of the six patients (33.3%) in the SLEDD group, and one of the six patients (16.7%) under SLEDD-f group (odds ratio, 0.40; 95% CI 0.03 to 6.18; p=0.512). The overall mortality rate was 25%. The risk factors associated for renal recovery include estimated glomerular filtration rate, etiology of acute kidney injury and serum creatinine level prior to the initiation of dialysis were found not significant by using logistic regression. Conclusion: SLEDD-f used in critically ill patients with acute kidney injury did not show any difference between SLEDD with regards to all-cause mortality and renal recovery. Thus SLEDD-f may be used as an alternative for patients in critical care settings.